2009
DOI: 10.1371/journal.pone.0008373
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Mycobacterium tuberculosis Lineages in Elderly Patients Born in Norway

Abstract: BackgroundDuring the previous century Norway had a high incidence of tuberculosis, but no molecular epidemiological studies could be performed and these previously epidemic strains have been disappearing during the last decades. Currently, tuberculosis among native Norwegians is in the elimination phase, and it is still not known what type of M. tuberculosis was so efficiently controlled during the second half of the 20th century. However, many elderly Norwegian-born people still develop TB that cannot be clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…This high prevalence of modern H, T and LAM strains is similar to the prevalence among isolates from patients born before 1950 in Norway, where a total of 40% of 213 isolates belonged to the T family and 35% to the H family [23]. As the Norwegian study, our study only included isolates displaying RFLP patterns not previously present in our database indicating an unlikely recent transmission.…”
Section: Discussionsupporting
confidence: 68%
“…This high prevalence of modern H, T and LAM strains is similar to the prevalence among isolates from patients born before 1950 in Norway, where a total of 40% of 213 isolates belonged to the T family and 35% to the H family [23]. As the Norwegian study, our study only included isolates displaying RFLP patterns not previously present in our database indicating an unlikely recent transmission.…”
Section: Discussionsupporting
confidence: 68%
“…Additionally, Finland – and other Nordic countries- had endured a very high tuberculosis incidence before the second world war [1]. As reported from Sweden and Norway, certain lineages (Haarlem and T) were predominately found among elderly cases, suggesting that these lineages were most likely associated with the epidemic during the first half of the 20 th century [15,16]. As found in this study, Haarlem and T were also the most common lineages found among Finnish born TB cases.…”
Section: Discussionmentioning
confidence: 99%
“…Among nonclustered native Dutch TB cases, Euro-American lineages were most frequently isolated. Domination of these lineages among native TB cases has also been shown in other European populations (19,20), suggesting that these lineages have been circulating in Europe for centuries (21). In contrast, recentimmigrant cases caused by nonclustered non-Euro-American strains originated from distant geographical areas.…”
mentioning
confidence: 81%